Sulfonyl hydrazone derivatives containing acetonaphtone as anticholinesterase inhibitors for the treatment of Alzheimer's: X-ray single-crystal analysis, and multifaced theoretical calculations - Ozmen, Ummuhan Ozdemir; Alyar, Saliha; Ayan, Esra Bilen; Canbolat, Nuveyre; Hamurcu, Fatma; Alyar, Hamit; Muhammet, Sinan Mithat; Hamurcu, Fatma (Elsevier, 2024)
In this study, the inhibitory activities of three different sulfonylhydrazone compounds (Anaf-salesh, Anaf-salpsh, Anaf-salbsh) obtained by using different alkyl sulfonic acid hydrazide and 2-Hydroxy-1-acetonaphthone on Acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes were examined. Among these compounds, 2-Hydroxy-1- acetonaphthone-ethanesulfonylhydrazone was investigated by X-ray diffraction. It crystallizes in the Triclinic system, space group P-1, a = 8.754(6), b = 9.042(7), c = 10.905(8) & Aring;, alpha = 71.88(2)degrees, beta= 76.27(2)degrees, gamma = 62.35(2)degrees V(& Aring;3)= 722.2 (9), Z = 2. Crystallographic results were evaluated using the B3LYP/6311++G** basis set and strong intermolecular interactions were observed. According to inhibition studies on enzymes, all synthesized compounds showed inhibitory effects on AChE and BChE enzymes. In particular, Anafsalbsh exhibited the best activity with an IC50 value of 11.51 +/- 0.21 mu M on AchE and 2,45 +/- 0.24 mu M BChE. The Molecules were optimized by DFT/B3LYP functionality and using the 6-311G ++ (d, p) basis set. Then, their activities against biological materials namely acetylcholinesterase (AChE) (PDB ID: 4PQE) and butyrylcholinesterase (BChE) (PDB ID: 6ESY) were compared. Molecular docking studies were performed to evaluate the binding interactions between the compounds and the enzymes. Molecular docking studies were conducted to investigate the binding interactions between the Anaf-salbsh compound, which demonstrates the best anticholinesterase inhibitor among the compounds, and both acetylcholinesterase and butyrylcholinesterase. This analysis provided valuable insights into the underlying binding mechanisms. Subsequently, ADME properties were investigated to test the drug properties.
Keywords: Acetonaphtone Sulfonylhydrazone; X-Ray Analysis; Choline Esterase Enzyme; Dft; Molecular Docking; Adme